A review of the ketogenic diet for endurance athletes: performance enhancer or placebo effect? - Bailey, C. P.; Hennessy, E. (Journal of the International Society of Sports Nutrition, 2020)
The ketogenic diet has become popular among endurance athletes as a performance enhancer. This paper systematically reviews the evidence regarding the effect of the endurance athlete`s ketogenic diet (EAKD) on maximal oxygen consumption (VO2 max) and secondary performance outcomes. Methods: PubMed and Web of Science searches were conducted through November 2019. Inclusion criteria were documentation of EAKD (< 50 g daily carbohydrate consumed by endurance athletes), ketosis achieved (measured via serum biomarker), VO2 max and/or secondary outcomes, English language, and peer reviewed-publication status. Articles were excluded if they were not a primary source or hypotheses were not tested with endurance athletes (i.e., individuals that compete at submaximal intensity for extended time periods). Study design, diet composition, adherence assessment, serum biomarkers, training protocols, and VO2 max/secondary outcomes were extracted and summarized. Results: Searches identified seven articles reporting on VO2 max and/or secondary outcomes; these comprised six intervention trials and one case study. VO2 max outcomes (n = 5 trials, n = 1 case study) were mixed. Two of five trials reported significant increases in VO2 max across all diets; while three trials and one case study reported no significant VO2 max findings. Secondary outcomes (n = 5 trials, n = 1 case study) were Time to Exhaustion (TTE; n = 3 articles), Race Time (n = 3 articles), Rating of Perceived Exertion (RPE; n = 3 articles), and Peak Power (n = 2 articles). Of these, significant findings for EAKD athletes included decreased TTE (n = 1 article), higher RPE (n = 1 article), and increased Peak Power (n = 1 article). Conclusion: Limited and heterogeneous findings prohibit definitive conclusions regarding efficacy of the EAKD for performance benefit. When compared to a high carbohydrate diet, there are mixed findings for the effect of EAKD consumption on VO2 max and other performance outcomes. More randomized trials are needed to better understand the potentially nuanced effects of EAKD consumption on endurance performance. Researchers may also consider exploring the impact of genetics, recovery, sport type, and sex in moderating the influence of EAKD consumption on performance outcomes.